Influences on the Seismic Response of the Gravity Dam-Foundation-Reservoir System with Different Boundary and Input Models - Denghong Chen; Chunping Hou; Feng Wang (Shock and Vibration)
Dynamic dam-foundation interaction is great important in the design and safety assessment of the dam structures. Two classic boundary conditions, i.e., the viscous-spring boundary and the viscous boundary, are employed to consider the radiation damping of the unbounded rock foundation. The input models of seismic excitation of the viscous-spring boundary and the viscous boundary are derived. The accuracy of the two boundary conditions in the dynamic analysis of the dam foundation is verified through the foundation analysis using an impulsive load. The influences of two boundary conditions and their earthquake input models on the seismic analysis of the Pine Flat and Jin’anqiao gravity dam-foundation-reservoir systems are then investigated. The results of displacements, hydrodynamic pressure, and principal stresses show that the agreement between the results of the viscous-spring boundary and viscous boundary is good. The relative errors of the two models in the Pine Flat and Jin’anqiao gravity dams are both less than 5%. They are both acceptable from an engineering point of view.